Analisis dan Desain Sistem Pengambilan Keputusan Pengangkatan Karyawan Tetap di PT. Aerofood ACS - Taufiq, Rohmat; Prasetyo, Rachmad Taufiq; Yusuf, Dadang (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2020)
Analysis and Design of the decision-making system for the appointment of permanent employees is done at PT. Aerofood ACS. The problem with appointment of permanent employees is that the selection process for permanent employees is still long, it is difficult to determine which employees should be taken if the number of qualified employees is more than needed. This research is a system analysis conducted with the aim to provide analysis and design results making it easier for management to develop into web-based applications. the method conducted in this research is by communicating with management and employees, determining problems, the process of finding data, making plans about the research to be carried out, conducting analysis followed by making a design proposal given to management, the latter being the process of making reports . The conclusion from the research carried out can find out how the process of hiring non-permanent employees to become permanent employees, giving design proposals to the management in detail so that hopes can be developed into a web-based decision support system that has the goal so that the system uses the most suitable method.